Systemic analysis of front Crawl stroke - Oliveira, Thiago A. C. de (2003)
The purpose of this study was to investigate the front crawl stroke at a behavioral level, ie arm stroke, leg stroke, and breathing components both separately and in interaction. Eleven adults aged 28 (P 4.25), experienced in front crawl stroke participated. They swam 10 meters at high speed and l0 meters at low speed. At both speeds, the variabilities of whole and parts were the measures considered. Data was analyzed through a Wilcoxon test, considering the following comparisons: whole versus parts at high speed; whole versus parts at low speed; whole at high speed versus whole at low speed; and parts at high speed versus at low speed. Results showed that at low speed the variability of parts was significantly superior to the variability of the whole, and therefore, that in interaction the behavior of arm stroke, leg stroke, and breathing varied less than each separately.